2003
DOI: 10.1016/s0741-5214(03)00716-x
|View full text |Cite
|
Sign up to set email alerts
|

Carotid ultrasound findings as a predictor of long-term survival after abdominal aortic aneurysm repair: a 14-year prospective study

Abstract: Patients electively operated on for AAA repair and with stenosis 50% or greater and echolucent plaque at duplex US scanning are at significantly increased risk for cardiovascular mortality and morbidity. Carotid US can therefore be used to select a subgroup of patients with AAA who might benefit from medical intervention, including antiplatelet and lipid-lowering agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
6

Year Published

2004
2004
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 36 publications
1
11
0
6
Order By: Relevance
“…In another study, it was shown that in 208 patients electively operated for an AAA, the presence of an asymptomatic CAS of 50% or greater was independently associated with vascular mortality (HRϭ3.6, 95% CIϭ1.3 to 10.1) and morbidity (HRϭ4.0, 95% CIϭ1.8 to 9.0). 13 These studies and our present study indicate that, overall, in patients with clinical manifestations of arterial disease, the presence of asymptomatic CAS (Ն50%) is a risk indicator of new vascular events. One of the differences between the previous studies and this study is that our study was conducted in a large prospective cohort of patients with well-defined diagnostic inclusion criteria of manifest arterial disease.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…In another study, it was shown that in 208 patients electively operated for an AAA, the presence of an asymptomatic CAS of 50% or greater was independently associated with vascular mortality (HRϭ3.6, 95% CIϭ1.3 to 10.1) and morbidity (HRϭ4.0, 95% CIϭ1.8 to 9.0). 13 These studies and our present study indicate that, overall, in patients with clinical manifestations of arterial disease, the presence of asymptomatic CAS (Ն50%) is a risk indicator of new vascular events. One of the differences between the previous studies and this study is that our study was conducted in a large prospective cohort of patients with well-defined diagnostic inclusion criteria of manifest arterial disease.…”
Section: Discussionsupporting
confidence: 76%
“…Two small studies, restricted to patients with coronary heart disease (CHD) or abdominal aortic aneurysm (AAA), also reported an increased risk of vascular death or MI in patients with asymptomatic CAS. 12,13 The aim of the present large prospective cohort study was to examine the relation between asymptomatic carotid artery stenosis and the risk of vascular events in patients with various clinical manifestations of arterial disease or presence of type 2 diabetes mellitus but without a history of cerebrovascular disease.…”
mentioning
confidence: 99%
“…Smaller studies have suggested that the incidence of severe coronary artery disease in people with an AAA remains at about 50 per cent 10 . The incidence of significant carotid artery stenosis among people with an AAA is much less, with one study reporting that only 25 per cent had stenosis of more than 50 per cent in at least one carotid artery 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Patients who suffer from carotid artery stenosis are more prone to develop clinically relevant atherosclerotic disease at other predilection sites compared with a healthy population [20][21][22][23]. For this purpose, duplex derived intima media thickness is often used as a surrogate endpoint in pharmaceutical studies [24].…”
Section: Rationalementioning
confidence: 99%